The Beliefs and Practices Embedded in the Pasanghid Ritual of the Talaandig Tribe - Judith Camino-Singcolan (Journal of Arts, Humanities and Social Science)
The language of the Talaandig tribe serves as a reflection of their identity. This paper explores the beliefs and customs of the Talaandig tribe in Lantapan, Bukidnon, as embedded in the language of their "Pasanghid" ritual. The study uses the ritual language as a framework to understand the tribe's identity and worldview. A qualitative design under descriptive research was employed, with an ethnographic approach for direct interaction and observation. Semi-structured instruments and open-ended questionnaires, adapted from Orobia (2013), were used to gather cultural terms and explore the tribe’s beliefs. The researcher participated in the "Pasanghid" ritual to gain a deeper understanding of its significance. The "Pasanghid" ritual involves offerings and prayers to the spirits, especially the "Apu" (ancestors), to seek permission and express gratitude. It reflects the Talaandig belief that communication with the spirits, including Magbabaya, the Supreme Deity, is essential for a prosperous life. Ritual terms, spoken by the baylan (ritual leader), are integral to these communications, preserving the tribe’s identity and cultural values. The study reveals that the ritual language is deeply tied to the tribe’s spiritual beliefs, highlighting the importance of ritualistic practices to maintain harmony and prevent misfortune. The findings recommend further studies on the language used in indigenous rituals, which could help preserve and promote the cultural heritage of the Talaandig tribe and other indigenous groups in the Philippines.